Artificial intelligence-based 3D dual-path prediction model for the stability of space mesh shell structures - Lin Xiao; Zhiqin He; Li Zhang; Yuhang Wang; Yuyao Huang; Bo Shen (Journal of Asian Architecture and Building Engineering)
The stability of space mesh shell structures has long been a central focus in structural engineering research. This paper introduces a 3D dual-path model based on artificial intelligence(AI) to assess the stability of these structures. The study employs ABAQUS finite element analysis software to simulate the dynamic responses of space mesh shell structures subjected to classical seismic waves, generating 500 time-history displacement datasets with equal proportions of stable and unstable structures. These datasets are then converted into RGB image sequences for model training, validation, and testing. The experimental results demonstrate the superior performance of the proposed model, with a precision of 0.93, recall of 0.92, an F1 score of 0.91, and an area under the curve (AUC) of 0.96, outperforming other models. Compared to traditional methods, 9 out of 10 datasets yielded consistent results. In conclusion, the model presented in this study provides a novel approach for future research into the stability analysis of space mesh shell structures.